Menavigasi Kedaulatan Digital: Model Diplomasi-Hibrida dalam Manajemen Public Relations di Era Disrupsi Telekomunikasi Satelit - Khairunnisa Nur Alifah; Sintia Rahmatasia; Lovina Hillan Tsaqila; Pramudya Ibnu Subrata (CITACONOMIA : Economic and Business Studies, 2026)
The rapid penetration of Starlink’s Low Earth Orbit (LEO) satellite technology in Indonesia has triggered a significant disruption within the national telecommunications landscape, sparking a conflict between global innovation and local protectionism. This conceptual article examines the strategic transformation of Public Relations (PR) from a traditional communication function into a sophisticated instrument of corporate diplomacy. By employing a descriptive qualitative method and grounded in Stakeholder Salience Theory, this study analyzes how global disruptors navigate rigid regulatory environments and economic nationalism. The findings reveal that Starlink’s success is not merely a result of technological superiority but is driven by a "Hybrid-Diplomacy" model. This model integrates political alignment with host country goals, strategic narrative shifting through the leverage of the "Celebrity CEO" persona, and strategic co-opetition with local stakeholders. The study proposes a new conceptual framework where PR practitioners act as architects of power relations, synchronizing corporate agendas with national digital transformation targets to secure a "Social License to Operate." This research concludes that in high-tech industries, political legitimacy often transcends conventional market approval. Future empirical research is recommended to validate this framework across diverse political systems and to isolate the influence of leadership branding from organizational PR strategies.